Postmodernity in contemporary Spanish poetry: The search for origins (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
The concept of postmodernity has become, in recent years, the philosopher!s stone of the arts. There is no contemporary artistic manifestation that does not come endorsed by this label, standard-bearer of an idea that is somewhat fluid and resistant to solidification. Is it possible nevertheless to establish an exact dating of the postmodern lyric? Do we have to connect postmodernity directly to a certain poetic generation? Or is it possible to talk about postmodern poems and poets while avoiding ideological and generational limits?
Keywords: posmodernity; spanish contemporary poetry; chronology